UNDANG-UNDANG NO. 21 TAHUN 2008 SEBAGAI SARANA REKAYASA SOSIAL DALAM PENYELESAIAN SENGKETA EKONOMI SYARIAH (Syariah: Jurnal Hukum dan Pemikiran, 2014)
This paper is about Law No. 21 of 2008 about Islamic banking as social engineering through: Verse (1) On Religious Courts as a dispute resolution of Islamic economics, Law becomes a tool to change the society. Before the emergence of that Law, the parties resolve the dispute with Islamic banks through other institutions. With that role, the Religious Courts are located as social engineering as "agents of change". It means that function of Law is run by Religious Courts. Verse (2), this rule aims to solve the disputes through kinships way and lose emotional as result of problems that occured. Verse (3), creating the society and sharia financial institution, which have disputes or solve it, make sharia the only law used.